1999
DOI: 10.1046/j.1365-2605.1999.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to diesel exhaust affects the male reproductive system of mice

Abstract: Several recent reports have suggested that sperm count and quality in normal men are declining. Various environmental chemical compounds may affect the male reproductive system. We propose here that diesel exhaust is an environmental pollutant with the potential to influence male reproductive function. Ultrastructural changes were observed in Leydig cells of mice exposed to diesel exhaust (0.3 mg diesel exhaust particles (DEP)/m3 through the airway, 12 h daily, up to 6 months) and reduction in LH receptor mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 22 publications
2
91
0
3
Order By: Relevance
“…Komatsu et al, have reported that Titanium oxide and carbon black nanoparticles were taken up by mouse Leydig TM3 cells, and affected the viability, proliferation and gene expression [49]. Yoshida et al reported that exposure to diesel exhaust nanoparticles induce Leydig cell degeneration, increase the number of damaged seminiferous tubules, and reduce daily sperm production [50].…”
Section: Discussionmentioning
confidence: 99%
“…Komatsu et al, have reported that Titanium oxide and carbon black nanoparticles were taken up by mouse Leydig TM3 cells, and affected the viability, proliferation and gene expression [49]. Yoshida et al reported that exposure to diesel exhaust nanoparticles induce Leydig cell degeneration, increase the number of damaged seminiferous tubules, and reduce daily sperm production [50].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe & Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002. While these studies have furnished epidemiologically important results, they have been done without knowledge of the bioactive entities in DEP, making it difficult to estimate the effect of individual components on human health.…”
Section: Introductionmentioning
confidence: 99%
“…This method provided two advantages in that no complex inhalation system was necessary and that whole body analysis was available. Either direct or indirect effects of injected DEP can reach the testis and reduce sperm production in male mice (H. Izawa, T. Kashiwagura and M. Sagai et al, manuscript in preparation), as can DEP exposure through inhalation of exhaust gas (Yoshida et al, 1999). Using this method of subcutaneous injection of DEP, we constructed two-directional subtraction libraries from the DEP-treated and control mouse testis poly (A) + RNA.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, inhaled DEP can have toxic effects on the reproductive system. For example, DEP have been reported to suppress spermatogenesis in rodents (Watanabe and Oonuki, 1999;Yoshida et al, 1999). Several studies have also shown that DEP have estrogenic and antiandrogenic activities (Kizu et al, 2003;Furuta et al, 2004;Taneda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%